2005
DOI: 10.1111/j.1399-3038.2005.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Early rapid weight gain and current overweight in relation to asthma in adolescents born with very low birth weight

Abstract: Early catch-up growth and subsequent overweight are suggested to be associated with later cardiovascular diseases and later type II diabetes. However, the impact of early catch-up growth and childhood overweight on the development of asthma has been less studied, particularly in children born with very low birth weight (VLBW). A birth cohort of 74 VLBW children (birth weight < or = 1500 g) was followed from birth and investigated on asthma at 12 yr of age. Early rapid weight gain was in one way defined as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 29 publications
1
46
1
4
Order By: Relevance
“…Eighteen studies were identified for full text review. Of those, twelve studies, listed in Table 1 by year, were excluded: six did not report physician-diagnosed asthma [33-38], two did not categorize overweight/obesity by BMI [39,40], one did not report incident asthma as the primary outcome [41], two reported only adult populations [42,43], and one used a cross-sectional analysis [44]. …”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies were identified for full text review. Of those, twelve studies, listed in Table 1 by year, were excluded: six did not report physician-diagnosed asthma [33-38], two did not categorize overweight/obesity by BMI [39,40], one did not report incident asthma as the primary outcome [41], two reported only adult populations [42,43], and one used a cross-sectional analysis [44]. …”
Section: Resultsmentioning
confidence: 99%
“…After reading the abstracts of these articles, we chose 27 for full reading. Of these, 10 were selected to be included in the present review (5,11–19).…”
Section: Resultsmentioning
confidence: 99%
“…It is an endogen protein whose role is related to the satiation's control, regulation of immune response, lung function, metabolism and micronutrients regulation. [23][24][25][26][27] Mai et al 28 assessed the concentration of leptin found in asthmatic and overweight children. It was observed that the low serum concentration was a protection factor to the development of asthma.…”
Section: Mechanisms Of Relation Between Obesity and Asthmamentioning
confidence: 99%